Celebrating Holy Week in the 19th Century Costa Rica - Méndez Alfaro, Rafael (2019)
The article seeks to offer a general overview of the way in which Holy Week was celebrated in the nineteenth century in Costa Rica, with emphasis in two particular moments; namely, mid and late of that century. For the first case, it is a set of stories and descriptions of European and North American travelers who traveled through Central American lands. Each of them left notes on the relief, fauna, flora and customs of the local populations. These sources have allowed to reconstruct, from the perspective of the traveling philanthropist, the religious traditions that were kept for "Easter week". For the analysis of the commemorations of Holy Week at the end of the 19th century, the written press was used. The emergence of the "diarism"; which is the regular publication of newspapers, towards the middle of the decade of 1880, constituted a valuable input for the dissemination of chronicles and reports on religiosity and institutionalized customs about Holy Week. The review of announcements and news notices in the immediately periods prior to the arrival of the Catholic solemnities, provides an accurate picture of the liturgical act that took place in the Josephine’s temples of that time. The Costa Rica of the late liberal century is a unique combination of tradition and modernity, where it is possible to appreciate the presence of rituals of colonial origin with traits of modernity, associated with the arrival of capitalism in the central valley. Therefore, it is not strange the survival of liturgical ceremonies full of protocol, mixed with the presence of multiple commercial announcements, which promote the sale of clothes, attire, accessories and allegorical meals of Holy Week.